Mobile communication research in communication journals from 1999 to 2014. (October 2017) - Kim, Yonghwan; Kim, Bumsoo; Kim, Youngju; Wang, Yuan
This study examined trends and patterns of mobile communication research across 10 communication journals between 1999 and 2014 with the intent to increase knowledge about mobile communication and to help scholars understand the future research directions. A total of 131 articles were coded for general information about journals, primary topic/context of the study, use of theories or models, research methods, units of analysis/types of sample, and countries or locations. Findings showed that the number of mobile communication-related studies increased over the time period of interest. Scholars examined uses and users' characteristics of mobile communication as well as the effects of mobile media on everyday life. Most studies used quantitative methods such as survey of the general population. Theories or theoretical models were not frequently used in mobile communication research. Regarding the usage of theories or theoretical models, about half of mobile communication studies (48.1%) used theories and/or models as theoretical frameworks. Implications for improving this field of research are specifically discussed.